Propolis as a natural alternative for food preservation: an integrative review of its antioxidant and antibacterial effects - Sousa, Antonia Mayara Brilhante de; Abreu, Virgínia Kelly Gonçalves; Ferreira, Adriana Gomes Nogueira; Santos Neto, Marcelino; Dutra, Richard Pereira; Pereira, Ana Lúcia Fernandes (Science & Technology Journals, 2023)
The presence of several bioactive compounds in propolis has been reported in the literature. These compounds have been described as directly related to their antioxidant and antibacterial activities. Thus, the use of propolis in the food production can be considered as an alternative for food preservation. The present study is an integrative review that was conducted in the following phases: elaboration of the orienting question for the research; literature search; data selection and extraction; data analysis; synthesis of results; and interpretation. For the literature review, some studies were obtained from the following databases: ScienceDirect, Web of Science, Scopus, and PubMed. For the elaboration of the research question, the PICo strategy was used, in which: P refers to the problem (propolis); I refers to the variable of interest (antioxidant and antibacterial effects); and Co refers to the research context (food preservation). Initially, 3421 studies were identified, out of which 15 were used for this review. For the antioxidant and antibacterial effects of propolis on different types of food, it was observed that 80% of the studies evaluated the antioxidant effect, while 33% evaluated the antibacterial effect. Most of these studies showed positive results. Therefore, propolis can be a viable alternative for the industry, as a way to increase food shelf life.